2009
DOI: 10.1128/jb.01701-08
|View full text |Cite
|
Sign up to set email alerts
|

Docking and Assembly of the Type II Secretion Complex of Vibrio cholerae

Abstract: Secretion of cholera toxin and other virulence factors from Vibrio cholerae is mediated by the type II secretion (T2S) apparatus, a multiprotein complex composed of both inner and outer membrane proteins. To better understand the mechanism by which the T2S complex coordinates translocation of its substrates, we are examining the protein-protein interactions of its components, encoded by the extracellular protein secretion (eps) genes. In this study, we took a cell biological approach, observing the dynamics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 59 publications
2
67
2
Order By: Relevance
“…3). Interestingly, a recent study on the type II secretion system of V. cholerae also showed discrete fluorescent foci along the cell periphery for different components of this macromolecular complex (37). This finding is in contrast to the polar localization pattern described earlier (22), which most likely resulted from an overexpression artifact (37).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…3). Interestingly, a recent study on the type II secretion system of V. cholerae also showed discrete fluorescent foci along the cell periphery for different components of this macromolecular complex (37). This finding is in contrast to the polar localization pattern described earlier (22), which most likely resulted from an overexpression artifact (37).…”
Section: Discussioncontrasting
confidence: 55%
“…Indeed, Lybarger et al concluded that "chromosomal, intraoperon expression conditions are optimal for determining the intracellular locations of fusion proteins" (ref. 37, p. 3149), and such conditions were used throughout this study.…”
Section: Discussionmentioning
confidence: 99%
“…To overproduce protein encoded by the VC1200 loci, plasmid pVesB was used (50). The plasmids were introduced into the wild-type and various isogenic mutants of V. cholerae N16961 (as indicated in the text) by triparental conjugation (29).…”
Section: Methodsmentioning
confidence: 99%
“…CT A and B subunits were separated under denaturating and reducing conditions as indicated. Immunoblots were primarily blocked in 3% BSA in TBS buffer (50 mM Tris, 200 mM NaCl, pH 8), followed by incubation with polyclonal anti-CT antibodies (1:5000; Sigma) using as a positive control purified cholera toxin (Sigma) and finally developed (50). Immunoblots were developed using typhoon Trio (Amersham Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, while results obtained in K. oxytoca and V. cholerae [42][43][44] with GFP-fused Gsp proteins indicate a circumferential distribution of the machinery into foci, the P. aeruginosa Xcp secreton was proposed to be polar. This was shown by adding a Lumino tag onto XcpR or XcpS or by the visualization of protease secretion with an intramolecularly quenched casein conjugate [45].…”
Section: Introductionmentioning
confidence: 99%